The shadow out of time - Lovecraft, H. P. (Howard Phillips), 1890-1937 (Weird fiction, 2020)
Miskatonic University, Arkham, 1908. Professor Nathaniel Peaslee collapses in front of a class of students, only coming to his senses five years later. Horrified to discover that his body has been far from inactive during the intervening period--and plagued by unsettling and outlandish nightmares--Peaslee attempts to piece together the truth behind the missing years of his life. A chilling journey through time, space, and the recesses of the mind, this newly reissued adaptation gives terrifying form to one of H.P. Lovecraft's final tales.